The detailed characterization of electrochemically switchable molecular assemblies on silicon electrodes - Ciampi, S.; James, M.; Choudhury, M.; Darwish, Nadim; Gooding, J. (R S C Publications, 2013)
In this paper we explore a multi-step synthetic strategy toward fabrication of monolayer-modified Si(100) electrodes that can be electrochemically switched. The synthetic scheme is modular and benefits from an established intramolecular lactonization scheme of benzoquinone analogs. A redox-tagged pendant group can be released from the surface such as to allow for in situ monitoring of the switch process. We show that this model system can be used to elucidate chemical and structural events for a surface dynamic system that is rapidly gaining popularity. The influence of polarization times, overpotentials and semiconductor doping type on the kinetic of the switch event is also investigated. In both basic and acidic aqueous electrolytes the release of suitable redox-active markers is found to require unexpectedly large cathodic overpotentials. The release event is accompanied by minor oxidation of the electrode surface and the switched constructs can be regenerated by chemical means with no appreciable deterioration of surface quality.